Shengfu Oil Enhances the Healing of Full-Thickness Scalded Skin Accompanying the Differential Regulation of β-Catenin, Dlk1, and COX-2 - Chen, Man-Tang; Yang, Yan-Jing; Li, Yu-Sang; Li, Xiao-Jun; Zhang, Wei K.; Wang, Jin-Ping; Wang, Xu; Tian, Gui-Hua; Tang, He-Bin (Frontiers in Pharmacology, 2017)
Shengfu oil is a traditional Chinese medicine formula containing sixteen ingredients, including Scutellariae radix, Olibanum, and Rehmanniae radix. In this study, we aimed to enhance the wound healing of rabbit full-thickness scalded skin by Shengfu oil and to elucidate its regulatory effects on β-catenin, Dlk1, and COX-2. We found that Shengfu oil exhibited significant anti-inflammatory, analgesic, and antimicrobial activities. The structure of wound tissues in Shengfu oil group was intact, including regenerated cutaneous appendages, indicating better healing capability of Shengfu oil compared to the controls. The protein expression of β-catenin, Dlk1 and COX-2 in wound tissues were investigated by immunohistochemistry staining and were further quantitated with the use of multispectral imaging analysis. The protein expression of β-catenin and Dlk1 in the Shengfu oil group was higher than that in the sesame oil group in early wound repair, accompanied by the lower expression of COX-2; the protein expression of β-catenin decreased in the middle of wound healing; the protein expression of β-catenin and Dlk1 increased at the end of wound healing. These results strongly suggest that Shengfu oil can enhance wound healing by regulating the expression of β-catenin, Dlk1, and COX-2 due to its excellent anti-inflammatory, analgesic, and antimicrobial activities.